Constituents of sea cucumber Holothuria (mertensiothuria) leucospilota brandt with broad antibacterial activities - Ceesay, Abdoulie (2013)
Compounds derived from natural products are unquestionable sources of antibacterial agents which could be used to combat the threats posed by pathogenic bacteria species in the phase of abrupt antibiotic resistance in the world. Holothuria leucospilota sea cucumber has been used in the past in traditional medicine as cure and remedy for illnesses. This research basically aimed at securing antibacterial compounds from H. leucospilota that can inhibit the growth of pathogenic human multidrug resistant bacteria species. Solvent combinations of methanol/acetone, isopropanol/ acetone and also ethanol/ distilled water, methanol/distilled water and isopropanol/ distilled water were used to improve the extraction of active constituents. Extracts from H.leucospilota were screened for antibacterial activity against staphylococcal cassette chromosome mec (SCCmec) clonally diverse Sequenced Type (ST) methicillin resistant Staphylococcus aureus (MRSA) of ST-1, ST-7, ST-22, ST-188, ST- 1283 including ST- 239 which was highly circulated in Malaysia and methicillin susceptible Staphylococcus aureus (MSSA) of ST-1, ST-5, ST-8, ST-80, ST-88 and ST-121 clones and also against extraintestinal pathogenic Escherichia coli (ExPEC) extended-spectrum beta-lactamase (ESBL) producing bacteria strains on which this extract has not been tested before. The disc diffusion and the broth micro dilution methods were used to conduct the preliminary susceptibility screening test. The conventional reduction in bacteria population to determine the bacteriostatic and bactericidal effects of the crude extracts,the time kill assay was used. The chemical screening of the extracts showed the presence of antibacterial chemical compounds classes such as terpenoids, phenols,steroids, alcohols, aldehydes, ketones, saponins, tannins and carbohydrates. Gas chromatography-mass spectrometry analysis revealed new and active antibacterial metabolites which have not been reported in this sea cucumber such as 2,4-bis (1,1- dimethylethyl)- phenol, 4-hydroxy-4-methyl-2-pentanone,, 3,7-dimethyl-2,6-octadienal-, (Z)- (citral), stigmast-5-en-3-ol, (3.beta.,24S)-, (sitosterol), acetic acid and methyl, 5,11,14,17-eicosatetraenoic acid. Some antibacterial compounds identified in the species were reported earlier such as hexadecanoic acid, arachidonic acid, eicosapentaenoic acid and oleic acid. The fatty acid analyses of the extracts showed the presence of (C8:0) to (C22:1) fatty acids methyl esters. The saturated methyl palmitate (44.86%) and the unsaturated cis-9-oleic methyl ester (45.0%) were revealed as main antibacterial components. The extracts of the body wall, Cuvierian tubules and visceral extracts exerted broad spectrum antibacterial activity against both the SCCmec Sequenced Type Gram-positive MRSA and ST MSSA clones and also the ExPEC ESBL producing Gram-negative bacteria. Minimum inhibition concentration (MIC) against these bacteria was ranged from 8 to 128 mg/mL and the minimum bactericidal concentration was ranged from 32 to >128 mg/mL which was comparable to values obtained in other studies especially in plant antimicrobial assays. Data from the time kill assay showed that the extract was bactericidal against the Gram-positive ATCC 700698 (MRSA) and ATCC 29247 (MSSA) bacteria after 12 hr interaction and after 8 hr interaction for Gram-negative ATCC 35218 (E. coli) bacteria and bacteriostatic after 6 hr interactions for both bacteria group. These results are also comparable to results obtained in other studies even though in some cases the reduction rate of bacteria load in this study appears slower. The results obtained from this work suggest that H. leucospilota sea cucumber could be a potential source of compounds that could be incorporated in ointments, dietary supplements as well as therapeutic and antibacterial agents.